Potentiated Opioid Analgesia in Norepinephrine Transporter Knock-Out Mice - Bohn, Laura M. (J Neurosci, 2000)
Several studies have shown that activation of α(2)-adrenergic receptors (α(2)ARs) leads to mild analgesic effects. Tricyclic antidepressants (TCAs), such as desipramine (DMI), which block norepinephrine transporters (NETs), also produce mild antinociception. The coadministration of either α(2)AR agonists or TCAs with opiates produces synergistically potentiated antinociception. It has been postulated that the analgesic effects of TCAs are determined by their ability to inhibit norepinephrine reuptake via interactions with the NET. To test this idea, we studied mice lacking a functional NET in spontaneous and morphine-induced antinociceptive paradigms. Morphine (10 mg/kg, s.c.) treatment produced greater analgesia, as assayed in the warm water tail-flick assay, in NET-knock-out (-KO) mice than in wild-type (WT) mice. As anticipated, yohimbine, an inhibitor of α(2)ARs, blocked this potentiation. Moreover, a warm water swim-stress paradigm, which is known to induce the release of endogenous opioids, produced greater antinociception in NET-KO than in the WT mice. Naloxone, an inhibitor of opioid receptors, blocked the development of the swim-evoked analgesia in both WT and NET-KO mice, confirming the involvement of the endogenous opioid system. In the NET-KO mice, DMI did not further enhance analgesia but was still able to produce inhibitory effects on the locomotor activity of these mutants, suggesting that the effects of this TCA are not exclusively via interactions with the NET. In summary, these results demonstrate in a genetic model that both endogenous and exogenous opiate-mediated analgesia can be enhanced by elimination of the NET, indicating that the interaction of TCAs with NET mediates these effects.